DOI: 10.25148/etd.fidc000125
|View full text |Cite
|
Sign up to set email alerts
|

Strain Promoted Click Chemistry of 8-Azidopurine and 5-Azidopyrimidine Nucleosides and Nucleotides with Cyclooctynes and Applications to Living Cell Imaging

Abstract: This dissertation, written by Jessica Zayas, and entitled Strain Promoted Click Chemistry of 8-Azidopurine and 5-Azidopyrimidine Nucleosides and Nucleotides with Cyclooctynes and Applications to Living Cell Imaging, having been approved in respect to style and intellectual content, is referred to you for judgment.We have read this dissertation and recommend that it be approved. The SPAAC methodology developed has also been applied to study the cellular targets in protozoal parasite, Trichomonas vaginalis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 101 publications
(108 reference statements)
0
1
1
Order By: Relevance
“…We observed strong blue fluorescence in live cells using excitation and absorbance filters 360/40 and 470/40 nm, respectively (Figure 5), which was comparable to the fluorescence that Ito et al observed during the reaction of 8-azido-cAMP and a difluorinated cyclooctyne in HeLa cells. 46 However, contrary to this report, we found that the use of transfection agents (e.g., Lipofectamine; see SI for discussion), which often results in cytosol fluorescence, undue stress, and morphological changes in cells, was unnecessary.…”
Section: ■ Results and Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…We observed strong blue fluorescence in live cells using excitation and absorbance filters 360/40 and 470/40 nm, respectively (Figure 5), which was comparable to the fluorescence that Ito et al observed during the reaction of 8-azido-cAMP and a difluorinated cyclooctyne in HeLa cells. 46 However, contrary to this report, we found that the use of transfection agents (e.g., Lipofectamine; see SI for discussion), which often results in cytosol fluorescence, undue stress, and morphological changes in cells, was unnecessary.…”
Section: ■ Results and Discussioncontrasting
confidence: 74%
“…These prerequisites are, however, unsuitable for biological applications including the potential medicinal applications because of the harsh conditions used and cytotoxic effect of the copper catalyst. 45,46 Moreover, the coupling between 5-azidouridine analogues and terminal alkynes are also scarcely developed, 47 mainly because of the photochemical instability of the 5-azidouracil substrates. 48 To overcome these limitations, the 5-(azido)methyluracil nucleosides were used instead to study the click chemistry of azidomodified pyrimidine bases.…”
Section: ■ Introductionmentioning
confidence: 99%